Upaya Guru Dalam Meningkatkan Hasil Belajar Pada Pembelajaran Bahasa Arab - Fita Ria; Doni Sastrawan; Kasmudi (Program Studi Pendidikan Bahasa Arab, 2021)
This research was conducted because there are still found some difficulties in learning Arabic. In this case, students still have the view on their mind that the Arabic is a language that is quite difficult to understand. In theory, the students have been able to distinguish the grammatically structure of noun (isim) and verb (fiil), but it was still found some errors when the teacher asked some questions related about it directly in the class. Yet, the some students still answered mistakenly, even though, they’ve known theoretically. Thus, it was found that there were still students who did not fully understand the material explained during the class. This study is not only aimed to determine the efforts that have been done by teachers in improving the values academic in learning Arabic language, but it is also to determine the extent of how student's abilities and their understanding in learning Arabic. This type of this research was descriptive research with a qualitative approach. This study will describe as accurate as possible toward the situation, facts or circumstances of an individual or group by describing the data with narrative text. This research was conducted at Darul Fattah Junior High School Bandar Lampung. Data collection methods used are interviews, observation, documentation and questionnaires. The results of the study indicated that both of the teachers and the school have made such a significant efforts to improve student learning outcomes, for example by giving new vocabularies intensively every day, providing more intensive individual study classes for students who still found difficulties in the material delivered in the class, helding an additional informal learning hours, and conducting a special mandatory language days in a week. Moreover, the teachers have also used methods and media maximally to attract their enthusiasm in learning. Thus, by these efforts done, most of the students have successfully achieved the standard learning outcomes in the class remarkably